PROBLEMATIKA PEMBELAJARAN AL-QUR’AN METODE QIRAATI DI TPQ FASTABIQUL KHOIROT DI DESA BLURU KIDUL SIDOARJO - Ayu Sofi; Istikomah Istikomah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
The purpose of this study is to analyze the problems of  learning the Qur'an using the Qiraati method at TPQ Fastabiqul Khoirot in Bluru Kidul Village in Sidoarjo and to identify the factors causing these problems. This study used a qualitative method with a descriptive approach. Data collection was carried out through interviews, observation, and documentation. The data analysis technique used the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that Al-Qur'an learning using the Qiraati method has been implemented in accordance with the learning stages, but several problems were still found, including differences in the reading abilities of students, lack of concentration during learning, limited learning time, and irregular attendance of students. In addition, the problems were also influenced by factors related to teachers, students, and parents, including the fact that there were still female teachers who did not have Qiraati certificates, so that the learning process was not yet running optimally.